Toisen kerran - Lumo (yhtye); Korhonen, Pete; Rasi, Ilkka; Sundström, Toni ([Helsinki] : Inkfish / EMI Finland, 2003)
11 kappaletta.
Lumo (yhtye): Pete, Toni, Heze, Ile, Janne.
[Äänite]
Keywords: Lumo (yhtye) -- albumit; rock